Are Malaysian Companies Ready for Environmental Practices? An Extension of Theory of Planned Behavior - Chan, Kar Hoong; Chong, Lee Lee; Ng, Tuan Hock (International Journal of Energy Economics and Policy, 2019)
Changes of climate and pollution globally have been the most concerning issue in the recent decades. The negative impacts of climate change and pollution towards the environment and human well-being have been significantly concern. Among them, Malaysia has been actively involved in looking for solutions to reduce the environmental degradation issues lately. This study adopted the extended Theory of Planned Behaviour (TPB), Norm Activation Model (NAM) and Maslow’s Hierarchy of Needs in examining the comprehensive motivational factors towards their intention to environmental practices. This study is aimed to provide insights related to the environmental practices among Malaysian companies specifically public listed companies. Questionnaires are distributed via email due to the location of the companies. The collected and usable data for this study is 107 companies. The targeted respondents are those who ranked manager and above from investor relations department. The data is being analysed by employing Partial Least Square-Structural Equation Modelling (PLS-SEM) in investigating the relationship between the motivational factors that influence companies’ environmental practices intention. The findings showed that corporate norm and actualisation needs are positively associated to the intention among companies to be environmental friendly. Keywords: Environmental Practices Intention, Attitude, Subjective Norm, Corporate Norm, Actualisation Needs, Government Policy, Extended Theory of Planned Behaviour JEL Classifications: P28, Q58 DOI: https://doi.org/10.32479/ijeep.8899